2015
DOI: 10.1016/j.ijheatfluidflow.2014.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Transient heating effects in high pressure Diesel injector nozzles

Abstract: The tendency of today's fuel injection systems to reach injection pressures up to 3000 bar in order to meet forthcoming emission regulations may significantly increase liquid temperatures due to friction heating; this paper identifies numerically the importance of fuel pressurization, phase-change due to cavitation, wall heat transfer and needle valve motion on the fluid heating induced in high pressure Diesel fuel injectors. These parameters affect the nozzle discharge coefficient (Cd), fuel exit temperature,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 40 publications
2
38
0
Order By: Relevance
“…Similar conclusions about the effect of the fuel properties have already been seen both experimentally and numerically for other kinds of biodiesel [27]- [31] and for winter fuel formulations [32]- [34]. Recently, a few authors [35]- [39] have showed that it is important to consider not only the changes in the fuel properties related to the fuel composition, but also those related to the different temperature and pressure conditions along the nozzle geometry, which are traditionally neglected.…”
supporting
confidence: 72%
“…Similar conclusions about the effect of the fuel properties have already been seen both experimentally and numerically for other kinds of biodiesel [27]- [31] and for winter fuel formulations [32]- [34]. Recently, a few authors [35]- [39] have showed that it is important to consider not only the changes in the fuel properties related to the fuel composition, but also those related to the different temperature and pressure conditions along the nozzle geometry, which are traditionally neglected.…”
supporting
confidence: 72%
“…Approaches have been made through one-dimensional modelling of the complete injector flow [9][10] [11] [12][13] [14] or three-dimensional modelling of the nozzle flow [4][15] [16][17] [18]. Some of these works assume that the flow is isothermal [11] [12][13] [14].…”
Section: Introductionmentioning
confidence: 99%
“…To accelerate this process and reduce costs, computational fluid dynamics (CFD) simulations are routinely used by manufacturers to evaluate, understand, and optimize FIE design and operation. Many numerical methods and approaches have been developed to simulate the performance of fuel injectors and provide insight into the physical processes taking place inside these systems [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Accurate simulation of the flow field within the FIE and phenomena observed further downstream (e.g., jet breakup and spray formation) is required to ensure their reliable predictive capability.…”
Section: Introductionmentioning
confidence: 99%